2001
DOI: 10.1210/jcem.86.9.7862
|View full text |Cite
|
Sign up to set email alerts
|

The Midgrowth Spurt in Healthy Children Is Not Caused by Adrenarche

Abstract: A small transient increase in growth, the midgrowth spurt, has been observed in several growth studies in healthy children around the age of 7 yr. During this time adrenarche (the physiological increase in adrenal androgen secretion) also occurs. Although it is now well established that estrogen, not androgen, has a critical role in the male (and female) pubertal growth spurt, a direct effect of androgens on growth cannot be excluded. In accordance with published observations that growth is frequently accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In normal children DHEA is related to the development of bone diameter in prepubertal children (Remer et al 2003(Remer et al , 2009, but see Remer et al 2004) but has little effect on skeletal growth (Reinehr et al 2006). Furthermore, adrenarche occurs approximately a year after the mid-childhood spurt (Remer and Manz 2001), ruling out increases in DHEA/S as a cause of such a growth spurt.…”
Section: Somatic Changes Associated With Adrenarchementioning
confidence: 99%
“…In normal children DHEA is related to the development of bone diameter in prepubertal children (Remer et al 2003(Remer et al , 2009, but see Remer et al 2004) but has little effect on skeletal growth (Reinehr et al 2006). Furthermore, adrenarche occurs approximately a year after the mid-childhood spurt (Remer and Manz 2001), ruling out increases in DHEA/S as a cause of such a growth spurt.…”
Section: Somatic Changes Associated With Adrenarchementioning
confidence: 99%
“…Physically, the mid‐childhood growth spurt was thought to correspond with adrenarche (Bogin, 1997; Parker, 1991), but Remer and Manz (2001) demonstrated that this growth spurt, if it occurs at all, is typically a year before levels of DHEA/S are detectable in circulation. DHEA/S is involved in the functioning of the immune system and may be protective against disease; specifically, elevated DHEAS levels are associated with decreased malaria density among pubertal girls (Leenstra et al, 2003), as well as increased resistance and lower density among pubertal males (Kurtis et al, 2001).…”
Section: Introductionmentioning
confidence: 99%